Does daytime sleepiness alter visual memory in schoolchildren aged 9 to 11 at different times during the school semester? (Research, Society and Development, 2021)
Daytime sleepiness could reduce the memorization of children who are in school. Thus, the aim of this study was to study the effect of daytime sleepiness on the visual memory of schoolchildren at different times during the school semester. Individuals of both genders (n = 88) aged 9 to 11 years and regularly enrolled at the Mariana Amália Municipal School were selected. Data collection occurred in two moments: at the beginning and end of the academic semester. A semi-structured questionnaire was used to collect sociodemographic information, the Epworth Sleepiness Scale to assess sleepiness and the Rey-Osterrieth complex figure, object recall, scrambling figures and addition of dictated numbers for memory analysis tests. The data revealed that there is no direct relationship between sleepiness and impaired memory by the tests used in any of the analyzed moments. However, children showed lower visuospatial memory efficiency at the beginning of the school semester, indicating that they may have greater difficulty in memory retention. Lastly, there was an abnormality in the degree of sleepiness at the end of the school semester and the female gender showed efficiency in immediate and late memory.